Asas Pertanggungjawaban Mutlak (Strict Liability) dalam Penuntutan Tindak Pidana Lingkungan oleh Korporasi - Brahmantiyo Rasyidi; Gunawan Nachrawi; Juwita Juwita (PT Elaborium Elevasi Indonesia, 2023)
Indonesia is a legal country that upholds its legal principles. So far, the understanding of law has focused only on rigid rules and legal systems, without considering their relationship to the issues that need to be resolved. In the face of continuous changing times, humans need to adapt and transform in an effort to stay afloat. development also produces adverse consequences for society itself. One of the common negative impacts associated with development is its impact on the environment. The development carried out often causes problems in maintaining environmental sustainability. Corporations are colloquially called corporatie, corporation, or corporate in latin. In a narrow sense, it can be interpreted as a legal entity that has the authority to act and do something. In Indonesia, there is an incident that is still a vivid example of environmental pollution by corporate companies. Corporate criminal liability as a subject of criminal acts faces challenges when law enforcement officials still base it on the principle of culpability, which means